Impacts of the Doha Development Agenda on People's Republic of China: The Role of Complementary Education Reforms - Fan Zhai; Thomas Hertel (Asian Development Bank (ADB), 2005)
This paper evaluates the poverty impact of mutlilateral trade liberalization under Doha Round WTO negotiation, using a household-disaggregated, recursive dynamic computable general equilibrium (CGE) model of the People's Republic of China (PRC). It explores how trade liberalization interacts with the reform of improving rural education. Simulation results show that multilateral trade reforms reduce poverty in the PRC, with biggest reductions occurring in the rural areas due to higher prices for farm products. Furthermore, the complementary reform on rural education generates substantial gains for the PRC's economy by boosting rural incomes and reducing the incidence of rural poverty significantly
hdl:11540/1899
Keywords: 330; Armut; Städtische Armut; Ländliche Armut; WTO-Recht; Handelsliberalisierung; China